2019
DOI: 10.1186/s40634-019-0198-0
|View full text |Cite
|
Sign up to set email alerts
|

Anteversion and length of the femoral tunnel in ACL reconstruction: in-vivo comparison between rigid and flexible instrumentation

Abstract: Background Due to it being tangential to the distal femoral axis, the anteromedial portal presents significant risk of causing iatrogenic damage, and of producing tunnels that are too short for optimal osseointegration. Flexible reamers were developed to eliminate the need for knee hyperflexion and offer better-controlled orientation of the femoral tunnel. We aimed to compare the anteversion and length of femoral tunnels drilled using flexible reamers to those drilled using rigid reamers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 26 publications
0
14
0
2
Order By: Relevance
“…Additionally, pins placed via AM-FR were significantly farther from the femoral origin of the LCL (26.1 mm vs 13.4 mm). Kosy et al, 20 Wein et al, 35 Dave et al, 5 Steiner and Smart, 33 and Tashiro et al 34 all found more anterior femoral tunnel exit points with the use of AM-FR compared with AM-RR. Larson et al 21 found no difference with regard to femoral tunnel exit point ( Table 7 ).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Additionally, pins placed via AM-FR were significantly farther from the femoral origin of the LCL (26.1 mm vs 13.4 mm). Kosy et al, 20 Wein et al, 35 Dave et al, 5 Steiner and Smart, 33 and Tashiro et al 34 all found more anterior femoral tunnel exit points with the use of AM-FR compared with AM-RR. Larson et al 21 found no difference with regard to femoral tunnel exit point ( Table 7 ).…”
Section: Resultsmentioning
confidence: 98%
“…Eight included studies 9 , 15 , 16 , 20 , 21 , 23 , 33 , 35 quantified femoral tunnel positioning by utilizing radiologic parameters. No studies reported any significant difference in the intra-articular femoral tunnel aperture location.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the outside-in technique, which allows the point of the outlets to be controlled on the femoral lateral surface, may be considered, this technique leads to acute graft bending, which is associated with poor graft maturation. 35 Therefore, for such knees, femoral drilling using the flexible reamer and curved guide system, which allows a certain degree of control over intra-articular tunnel orientation 36 and can produce significantly more anteverted femoral tunnels than those obtained with a rigid drill 37 or other fixation methods such as anchors or staples, may be better.…”
Section: Discussionmentioning
confidence: 99%